2014
DOI: 10.4018/ijsita.2014010102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Implementation of Factors Affecting e-Governance Adoption in the Kingdom of Saudi Arabia

Abstract: For the last five years, the Kingdom of Saudi Arabia has taken a leading role in the Middle East in providing effective electronic government (e-government) services and encouraging their use. The global average for government website usage by citizens is about 30%. The vast majority of Saudi citizens visit government offices to obtain information rather than making transactions through government portals. However, it is apparent that the rate of global e-government adoption has fallen below expectations, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…For example the Gulf Cooperation Council (GCC) Arab countries share common characteristics in terms of customs and traditions, living standards, high penetration rate of mobile phones, high quality infrastructure, and thus constitutes a good context to conduct a cross Arab culture in order to ascertain the homogenous of the Arab culture. Furthermore, as past studies have proven that culture affects technology adoption, this study encourages future studies to expand and test the research model to other European cultures (e.g., Poland) using the SEM, in order to assess the validity of the proposed model since very few studies have shown that differences in e-government adoption exist across cultures (Al-Maliki, 2014). Therefore, we suggest to continue investigating factors that influence IR e-government by comparing the behavior of users from other countries in order to increase our understanding of the similarities and differences in e-government behavior.…”
Section: Research Perspectivesmentioning
confidence: 90%
“…For example the Gulf Cooperation Council (GCC) Arab countries share common characteristics in terms of customs and traditions, living standards, high penetration rate of mobile phones, high quality infrastructure, and thus constitutes a good context to conduct a cross Arab culture in order to ascertain the homogenous of the Arab culture. Furthermore, as past studies have proven that culture affects technology adoption, this study encourages future studies to expand and test the research model to other European cultures (e.g., Poland) using the SEM, in order to assess the validity of the proposed model since very few studies have shown that differences in e-government adoption exist across cultures (Al-Maliki, 2014). Therefore, we suggest to continue investigating factors that influence IR e-government by comparing the behavior of users from other countries in order to increase our understanding of the similarities and differences in e-government behavior.…”
Section: Research Perspectivesmentioning
confidence: 90%
“…This research study's goal is to determine the effects of ICT investment in Saudi Arabia and the role that the government plays in this context. According to another study by Al-Maliki [12] the adoption of e-governance in Saudi Arabia is influenced by a number of factors, Lack of training and human resources, together with limited computer literacy, were identified to be the main obstacles to adoption. Al-Maliki [11] also indicates that difficulties with literacy, technical issues, and a lack of knowledge and trust may be the main obstacles to the growth of this kind of business in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The only routes were via neighboring Gulf nations like the United Arab Emirates or Bahrain. Over time, email along with internet-based networks becomes indispensable to the majority of Saudi enterprises for doing daily business (Al-Maliki, 2013). ICT promotion has been of the utmost importance.…”
Section: Saudi Arabia's Technological Infrastructurementioning
confidence: 99%
“…However, there have been several obstacles in Saudi Arabia when it comes to integrating technology into the classroom. Keeping up with technological advancements has been the main challenge, requiring more time, money, and human resources (Al-Maliki, 2013). According to Almalki and Williams (2012); Alshumaimeri (2019), Saudi Arabia, being a developing nation, lacks the technological infrastructure of industrialized nations, and there is a general dearth of study on the barriers to ICT adoption (Almaliki, 2013).…”
Section: Saudi Arabia's Technological Infrastructurementioning
confidence: 99%